Source forensics of inorganic and organic nitrogen using δ15N for tropospheric aerosols over Mt. Tai - Libin Wu (Nature Portfolio, 2021)
Abstract Nitrogen-containing species are major components in atmospheric aerosols. However, little is known about the sources of N-containing aerosols over high mountainous regions, especially for organic nitrogen (ON). This study aims to reveal the emission sources of both inorganic and organic nitrogen in tropospheric aerosols atop Mt. Tai, China, and to improve our understanding of the N cycle imbalance in the North China Plain (NCP). Total suspended particle (TSP) samples were collected on a daytime/nighttime basis in spring 2017 and were investigated for the concentrations and stable N isotopic compositions of total nitrogen, NH4 +, NO3 − and ON. Our results show that the concentrations of N-containing compounds were higher in daytime than nighttime, mainly resulting from mountain–valley breezes and the changes of planetary boundary layer height. However, no significant day/nighttime changes were found for their corresponding δ15N values, indicating similar contributions from different N sources between day and night. The MixSIAR Bayesian stable isotope mixing model results suggest that the most important emission source of NH3 for aerosol NH4 + was agriculture, followed by fossil fuel-related sources, human waste and biomass burning. Aerosol NO3 − was mainly formed from combustion and mobile emitted NO x . Interestingly, the isotopes of ON suggest that ON were very likely firstly of primary origin. Our study reveals the characteristics of reactive N emission sources and helps understand the regional transport of tropospheric N-containing aerosols in the NCP.